1998
DOI: 10.1063/1.367098
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of (PMN)(1−x)(PT)x single crystals for various electrical and thermal histories

Abstract: Dielectric investigations of the (PMN)(1−x)(PT)x crystalline solution have been performed for various electrical histories. For x<0.3, relaxor behavior was observed, however the degree of diffuseness in the dielectric maximum and degree of relaxor characteristics were decreased with increasing x. Application of dc bias for x<0.33 (xc) resulted in an induced transformation to a long-range ferroelectric state. This transition had a critical threshold field (Eth). The value of Eth depended on x. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(106 citation statements)
references
References 21 publications
9
97
0
Order By: Relevance
“…Details of dielectric studies have been described elsewhere. 5,7 The majority of our experimental data have been obtained in the 1 -100 kHz frequency range. It is well documented in the literature that, in the case of the PMN-PT compositions, this range is wide enough to demonstrate the frequency dispersion of permittivity and the frequency shift of T m .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of dielectric studies have been described elsewhere. 5,7 The majority of our experimental data have been obtained in the 1 -100 kHz frequency range. It is well documented in the literature that, in the case of the PMN-PT compositions, this range is wide enough to demonstrate the frequency dispersion of permittivity and the frequency shift of T m .…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that, 5,[8][9][10] for PMN-xPT compositions within the morphotropic phase boundary ͑MPB͒ range, the temperature T m of the permittivity maximum increases with dc bias field E and the rate of this increase depends on the crystal orientation. Contrary to this, Viehland et al 16 showed that, in PMN-0.1PT ceramics, T m slightly decreases under small fields and strongly increases only at large fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some details of dielectric studies of other PMN-PT crystals have been described elsewhere. 13,14 Though we focus mainly on the results obtained in the zero field cooling (ZF) and field cooling (FC) modes, field heating (FH), and zero field heating after field cooling protocols were used as well. The temperature dependences of the complex dielectric permittivity ε(T ) measured in the ZF mode for both PMN and PMN-PT30 single crystals have one diffused frequency-dependent maximum at about 260 K and 400 K ( at 1 kHz), respectively (see for details Refs.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Very recently, it was found that the binary Ti-Ni STG exhibit a new shape memory effect and superelasticity, which is originated from a stress-induced transition from STG (with R-like local order) to a long-range strain ordered phase, B19' (monoclinic) martensite 11 . It shares the same physical origin as the field-induced transition in relaxor, whereas the order parameter is polarization [16][17][18] . 3 For binary Ti-Ni STG, although it is conceivable that a local order can be changed into a long-range order by stress, it remains a puzzle why the R-like local order does not transform into an R-phase (with the same strain order), and why it changes into a B19' martensite (with different strain order).…”
Section: Introductionmentioning
confidence: 99%